Urban shrinkage in Leipzig, Germany: Research report, EU 7 FP project Shrink Smart (contract no. 225193), WP2 - Dieter Rink; Annegret Haase; Matthias Bernt; Thomas Arndt; Johanna Ludwig (Helmholtz-Zentrum für Umweltforschung (UFZ), 2011)
This report describes the process of shrinkage as it has occurred within the city of Leipzig. It examines the reasons, dynamics and patterns of change as well as the consequences for different fields of urban development and planning. The period covered in the report runs from the 1980s to the present day; in particular cases, longer or shorter time periods are considered. Over this time, Leipzig has moved from a (more or less rapidly) shrinking city until the late 1990s to a point where ist population stabilized and even returned to a slight growth during the last few years. Today, Leipzig is no longer a shrinking city. When one looks only at the total population numbers, Leipzig represents one of a few large cities in eastern Germany that have undergone reurbanization processes (Haase, A. et al. 2010). However, urban shrinkage continues to be an important topic for the city. The city is still facing the consequences of long-term shrinkage and will have to cope with it during the years to come. At the same time, shrinkage still affects some parts of the city and will also do so in the future. Moreover, Leipzig awaits a new wave of shrinkage due to ageing and a decrease in households after 2015.
Keywords: 330